Phytoplankton taxon-specific growth and microzooplankton grazing rates in subantarctic HNLC waters on and off Campbell Plateau southeast of New Zealand during austral autumn - Andrés Gutiérrez-Rodríguez; Mikel Latasa; Karl Safi; Matt Pinkerton; Scott D Nodder (PANGAEA, 2023)
Here we present data of phytoplankton pigment and flow cytometry (FCM) data in the water column (CTD_HPLC_FCM_May2022.xlsx) and dilution grazing experiments (DILEX_HPLC_FCM_Conc_May2022.xlsx), and derived apparent growth rates for specific pigment markers and picophytoplankton groups assessed by FCM (APPARENT_GROWTHRATES_May2022.xlsx). Samples and experiments were collected and carried out in subantarctic waters across the Campbell Plateau region southeast of New Zealand. We distinguish between a subset of extquotesingleExperimental extquotesingle stations (n = 8), where serial dilution experiments were conducted and a subset of additional extquotesingleBiomass extquotesingle stations (n = 7), where depth-resolved physico-chemical and biological measurements (e.g., nutrients, size-fractionated chlorophyll a (SF-Chla), optical microscopy, FCM and HPLC) were also undertaken throughout the euphotic zone. extquotesingleExperimental extquotesingle stations were used to characterize phytoplankton group-specific growth and grazing rates and associated carbon production and microzooplankton consumption dynamics in surface-mixed layer waters (10 m) On-plateau (n = 5) and Off-plateau (n = 3) with extquotesingleBiomass extquotesingle stations providing a broader context of the environmental conditions and phytoplankton biomass and taxonomic composition across the region.